2006
DOI: 10.1007/s00586-006-0170-4
|View full text |Cite
|
Sign up to set email alerts
|

The vertebral endplate: disc degeneration, disc regeneration

Abstract: The vertebral endplates are critical for maintaining disc function yet like other components of the disc are vulnerable to degeneration. This paper provides an overview of the development and normal function of the endplates as well as an impression of what happens when they undergo progressive degeneration. Recent research suggests that the degenerative process can be retarded or reversed.Keywords Disc AE Endplate AE Degeneration AE Regeneration ManuscriptDespite all that is known from decades of research the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
159
0
6

Year Published

2006
2006
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 211 publications
(166 citation statements)
references
References 55 publications
1
159
0
6
Order By: Relevance
“…The endplate is important in maintaining the integrity and functions of the intervertebral disc [3], and its morphology, which is less well known, could have practical relevance, such as for disc arthroplasty. It has been suggested that endplate morphometrics, especially the degree of concavity and concordance between the two endplates adjacent to a disc, may be important to artificial disc design [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…The endplate is important in maintaining the integrity and functions of the intervertebral disc [3], and its morphology, which is less well known, could have practical relevance, such as for disc arthroplasty. It has been suggested that endplate morphometrics, especially the degree of concavity and concordance between the two endplates adjacent to a disc, may be important to artificial disc design [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…For anyone involved in the basic science of the disc this supplement brings many strands of basic science together, genetics [11], degeneration imaging [4] tissue repair [22], senescence [43], regeneration [36] and much other work on the basic science of the disc, and its elucidation.…”
Section: Back Painmentioning
confidence: 99%
“…However, at present such approaches to humans are still rare and limited due to remaining concerns about safety and biological potency. Although tremendous efforts have been made to improve disc cell therapy, today's results are rather disappointing with early loss of implanted cells caused by annular damage at the injection site and cell death due to the harsh intradiscal environment characterized by insufficient nutrition, accumulation of waste products and high intradiscal pressures [3][4][5][6][7]. Additionally, cell-based strategies are expensive, time demanding, and invasive with potentially more complications, since autologous cells have to be collected in a first operation, with the need for processing and cultivation, and then application to the disc in a second operative procedure.…”
Section: Introductionmentioning
confidence: 99%